HIV-1 integrase inhibitors - Markowitz, Martin (Henry Stewart Talks, 2011)
HIV integrase and the viral life cycle, General features of integrase inhibitors, Clinical profiles of clinically relevant strand transfer integrase inhibitors, Raltegravir, elvitegravir and s/GSK 572, Resistance and cross resistance to integrase inhibitors